The The Relationship between Hypertension and Anxiety Level in the Elderly in Mandungan Srimatani Sub-district Piyungan Bantul Regency Yogyakarta - Isnaeni, Yeni; Nur Adkhana Sari, Dian; Nur Hartiningsih, Sri (Java Nursing Journal, 2023)
ABSTRACT Background: Hypertension is still a problem for the elderly, the changes experienced by the elderly will experience a lot of decline, both physically, mentally, and socially. As an age that shows the aging process, this condition makes high blood pressure a health problem for the elderly. A person is said to have hypertension and has a systolic and diastolic blood pressure of 140/90 mmHg. Hypertension is often found in the elderly, the physical limitations experienced by the elderly will experience anxiety because the various diseases they suffer do not go away and even get worse in the end they experience psychological disorders, namely anxiety, which is marked by deep and ongoing fears and worries. Objective: To determine the relationship between hypertension and anxiety levels in the elderly in Mandungan Srimartani Hamlet, Piyungan District, Bantul Regency, Yogyakarta. Methods: This research is non-experimental with a correlation study using a cross sectional approach, and the sample size is 39 respondents aged 60-80 years. Results: The data that has been analyzed using the Kendall-Tau test has a correlation coefficient value of 0.483** and a significant value of 0.001 < 0.005. Conclusion: There is a relationship between hypertension and anxiety levels in Mandungan Srimartani Hamlet, Piyungan District, Bantul Regency, Yogyakarta. Keywords: Hypertension, Anxiety Level, Elderly